An in vitro analysis on the antioxidant and anti-diabetic properties of Kaempferia galanga rhizome using different solvent systems - S Vishaka; G Sridevi; J Selvaraj (Wolters Kluwer Medknow Publications, 2022)
Kaempferia galanga rhizome (KGR) is a stemless, sweet-smelling, enduring, and rhizomatous monocotyledonous plant of the ginger family also called sand ginger or kencur. lt possesses many pharmacological effects and the goal of this study is to use several solvent solutions to determine the antioxidant and anti-diabetic potential of KGR. By observing KGR's alpha-glucosidase and alpha-amylase inhibitory activity, the in vitro diabetic activity was assessed. The in vitro cancer preventive action was evaluated by doing the 2,2-diphenyl-1-picrylhydrazyl test. The outcomes of the study showed increase in dose-dependent percentage of inhibition in α-amylase and α-glucosidase activity for both extract and standard ranging from 100 to 500 μg/ml. The current review proposes that the concentrate of KGR could be utilized for the treatment of diabetes mellitus as well with respect to dealing with the oxidative stress-related diseases.